The Effect of Achievement Motivation and Self-Regulated Learning on Student Learning Behavior in the Time of Online Learning in Indonesia - Hindradjat, Juliana; Hambali, Imam; Atmoko, Adi; Livana, P. H. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Self-regulated learning (SRL) and achievement motivation are important variables in students’ learning behavior. AIM: The purpose of this study was to examine the effect of achievement motivation and SRL on the learning behavior of junior high school students in Indonesia during the online learning period. METHODS: The research uses a quantitative approach with a causal associative research design. The research population is junior high school students in grades VII, VIII, and IX from various regions in Indonesia during the online learning period. Research respondents total 2,880 students, who were selected through random sampling technique. Respondent data were collected using a set of questionnaires in the form of a validated achievement motivation scale, SRL, and learning behavior, and processed and analyzed using the path-analysis method. RESULTS: The results of statistical processing show that the correlation coefficient between Achievement Motivation and SRL is 0.432 with a significant relationship and is included in the category of a fairly strong relationship. The correlation coefficient between Achievement Motivation and Learning Behavior is 0.632 with a significant relationship and is included in the category of a strong relationship. The correlation coefficient between SRL and Learning Behavior is 0.675 with a significant relationship and is included in the category of a strong relationship. Based on the Path Analysis Calculation Result Table, the path coefficient value for Achievement Motivation is 0.418 with a positive relationship direction. Simultaneous test results obtained the conclusion that there is an influence between Achievement Motivation and SRL variables on Learning Behavior of 59.8%, while the remaining 40.2% is the influence of other variables not involved in this study. The direct influence of Achievement Motivation on Learning Behavior is 17.5% and the indirect effect through SRL is 8.9%, so that if added up, the total effect is 26.4%. Then, the direct influence of SRL on Learning Behavior is 24.4% and the indirect effect through Achievement Motivation is 8.9% so that if added up, the total effect is 33.4%. CONCLUSION: There is a significant effect between achievement motivation and SRL on student learning behavior simultaneously; there is a significant influence between achievement motivations on student learning behavior partially. There is a significant influence between SRL on Student Learning Behavior partially.